Review of the genus Saprinus Erichson, 1834 from Madagascar and adjacent islands with description of a new species (Coleoptera: Histeridae: Saprininae) Third contribution to the knowledge of the Histeridae of Madagascar - Lackner, Tomáš; Gomy, Yves (Zootaxa, 2016)
Clown beetles belonging to the genus Saprinus Erichson, 1834 from Madagascar and adjacent islands are reviewed. The Malagasy fauna of Saprinus consists of seven species: Saprinus (Saprinus) erichsonii Marseul, 1855; Saprinus (Saprinus) fulgidicollis Marseul, 1855; Saprinus (Saprinus) basalis Fairmaire, 1898; Saprinus (Saprinus) cupreus Erichson, 1834; Saprinus (Saprinus) chalcites (Illiger, 1807); Saprinus (Saprinus) splendens (Paykull, 1811); one species S. (Saprinus) labordei sp. nov., is described as new. Saprinus erichsonii Marseul, 1855 is transferred from the subgenus Phaonius Reichardt, 1941 into the nominotypical subgenus based on the morphological evidence. Lectotypes of the following species are designated: Saprinus erichsonii Marseul, 1855; Saprinus basalis Fairmaire, 1898 and Saprinus fulgidicollis Marseul, 1855. Saprinus (Saprinus) cupreus Erichson, 1834 is newly reported from Madagascar and Saprinus (Saprinus) basalis Fairmaire, 1898 is newly reported from the following countries: Congo, Gambia, Central African Republic, Namibia, Zimbabwe and Republic of South Africa.